Hitokoma Kanji App as a Direct Corrective Feedback Medium - Noviyanti Aneros; Esthi, Arvina Tri; Renariah, Renariah; Juangsih, Juju (Universitas Negeri Semarang, 2024)
In the current era, technology is utilized for various activities, including learning. Learning applications are one such example, and they can be used as a medium for self-learning and corrective feedback. This study utilized an application called Hitokoma Kanji for kanji writing practice. The research sample consisted of 14 participants from second-year students of the Department of Japanese Language Education at FPBS UPI. This study aims to find out the process of kanji writing practice and corrective feedback using the Hitokoma Kanji application for four meetings. The method used in this research is qualitative. This research is explorative or preliminary, so the data taken is based on observation activities through screen recordings to understand how the Hitokoma Kanji application can affect kanji learning rather than conducting tests. The result of this study is the use of the Hitokoma Kanji application as a kanji writing practice media, and the Extrusion/Lenght Check feature helps participants to remember the order of scribbles and the shape of scribbles on kanji by the writing rules.